The Effect of Profitability, Liquidity, and Capital Structure on Timeliness of Submitting Financial Reports - Ni Komang Trisna Dewi; Putu Agus Ardiana (E-Jurnal Akuntansi, 2025)
This research aims to identify the impact of profitability, liquidity, and capital structure on the timeliness of financial report submission in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2019 period. The study population consists of 190 companies, and the sample was selected using purposive sampling, resulting in 80 observations. Data analysis was conducted using logistic regression. The results indicate that profitability, liquidity, and capital structure have a positive and significant effect on the timeliness of financial reporting. Company age, as a control variable, also has a positive and significant effect, while company size and managerial ownership show no significant influence.